2021
DOI: 10.1007/978-3-030-73103-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Anonymity in COVID-19 Online Donations: A Cross-Cultural Analysis on Fundraising Platforms

Abstract: Donating money anonymously is often perceived as an act of altruism in Western culture and a similar concept of 'ikhlas' (sincerity) in Indonesia. Yet, this prosocial behavior can also be utilized to cope with unpleasant feelings associated with such donations (e.g., fear of social judgment, guilt) making it otherwise a rather self-serving act. In that regard, we analyzed 20,000 individual donation transactions made for COVID-19 campaigns on two popular fundraising platforms: GoFundMe in the United States and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A research in Indonesia uncovered a compelling phenomenon wherein self-identified donors contributed significantly more money on online donation platforms than did their anonymous counterparts [3]. An experimental study demonstrated that individuals with a high interdependent self-construal were inclined to make donations when their actions could be observed in a public context, driven by a desire to portray themselves as caring individuals [36].…”
Section: Eudaimonic Hedonic and Extrinsic Motives Of Happiness And Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A research in Indonesia uncovered a compelling phenomenon wherein self-identified donors contributed significantly more money on online donation platforms than did their anonymous counterparts [3]. An experimental study demonstrated that individuals with a high interdependent self-construal were inclined to make donations when their actions could be observed in a public context, driven by a desire to portray themselves as caring individuals [36].…”
Section: Eudaimonic Hedonic and Extrinsic Motives Of Happiness And Pr...mentioning
confidence: 99%
“…According to a 2022 Expat Insider survey, Indonesia is the second most friendly country in the world where expatriates or foreign workers feel treated kindly as foreigners and do not find it difficult to make friends [2]. Anonymous donations during the COVID-19 outbreak were more widespread in Indonesia than in the U.S. [3]. Other data also showed that the participation of Indonesian Gen-Z (born between 1997 and 2012) in online donations increased [4].…”
Section: Introductionmentioning
confidence: 99%
“…hate speech [5], political preferences [6], climate change [7], domestic violence [8], pop culture [9], cybersecurity and privacy [10], online donations [11], and online fraud [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, digital footprints on social media capture things as they have occurred, which is not always the case in traditional approaches like surveys and interviews. As a result, these digital footprints have also been extensively employed to study a wide range of social topics on the internet and in particular on social media over the past decade, including those that are quite sensitive such as anonymous online donations ( Firmansyah & Pratama, 2021 ), racial digital identities ( Firmansyah & Jones, 2019 ), and political preferences ( Oliveira, Bermejo & dos Santos, 2017 ).…”
Section: Introductionmentioning
confidence: 99%